Resources within Spiritual and Mystical Christian Traditions for the Care of Earth – our Common Home - Sadowski, Ryszard F. (Studia Ecologiae et Bioethicae, 2020)
Research on the ecological crisis has revealed its global and total character, which implies that any attempts at overcoming it must take into account a wide variety of perspectives. It is not surprising, therefore, that for several decades the study of the ecological crisis has been undertaken by philosophers and religologists who seek inspirations for ways to shape an environmentally friendly lifestyle in various religious traditions. Notwithstanding the prevailing stereotypes as regards Christianity and its allegedly anti-ecological attitudes, there are many indications that this rich religious tradition has a lot to offer in the battle against the environmental crisis. The aim of this study is to present four Christian models of human relations with nature, which confirm the great ecological potential of Christianity. Those include: 1) Celtic animate model; 2) Benedictine custodial model; 3) Nuptial model of Hildegard of Bingen; and 4) St. Francis' fraternal model.